Transcriptional variation in human malaria parasites and its association with drug resistance - Mok, Sachel (2013)
A number of studies have been carried out to study transcriptional variation in P falciparum ranging from in vitro profiling of culture-adapted strains to drug perturbation experiments. Transcriptional variation is largely stochastic and not a directed transcriptional response in clones. Yet in field isolates, transcriptional profiles associated with distinct metabolic states are observed, which may reflect diversifications in the physiology of the cell depending on individual host cell conditions such as nutrient availability and host immune responses. Hence, we propose that these metabolic states may be involved in drug resistance phenotype. Using microarray technology, we first established an infrastructure to investigate transcriptional changes between clones of a culture-adapted strain 3D7. Additionally, we aimed to identify transcriptional changes that occur in the process of adapting a field isolate to culture. In this respect, we utilized this infrastructure to determine cell-specific responses to in vitro culturing which represented a change in growth conditions. Surprisingly, we observed large and significant overlaps in genes showing transcriptional changes between clones and between generations of a culture adapted clone at the qualitative level. They mainly comprise of genes coding for host cell remodeling factors such as Maurer’s cleft exported proteins, invasion-related, protein kinases and genes for sexual stage development. There was no particular pathway or gene that was selected for over the course of in vitro culturing, suggesting that these changes are not directed transcriptional responses to changing growth conditions. Whether this stochastic expression helps it to survive remain unanswered. More importantly, we observed that major transcriptional differences between isolates were maintained in culture throughout the generations which include the differential expression of two drug-resistance candidate genes belonging to the folate biosynthesispathway. Taken together, we have defined a set of genes known to be differentially expressed between any two parasite lines or between generations. On another note, using our microarray infrastructure, we established transcriptional profiles of in vivo isolates from South East Asia and identified key features associated with clinical artemisinin resistance which has emerged in Western Cambodia. In the ring and trophozoite stages, we observed reduced expression of many basic metabolic and cellular pathways which suggests a slower growth and maturation of these parasites during the first half of the asexual intraerythrocytic developmental cycle (IDC). In the schizont stage, an increased expression of essentially all functionalities associated with protein metabolism may indicate the increased capacity of protein synthesis during the second half of the resistant parasite IDC. This modulation of the P. falciparum intraerythrocytic transcriptome may result from differential expression of regulatory proteins such as transcription factors or chromatin remodeling associated proteins. In addition, there is a unique and uniform copy number variation pattern in the Cambodian parasites which may represent an underlying genetic background that contributes to the resistance phenotype. Our microarray analyses of the clones also revealed significant transcriptional variation of a drug transporter gene coding for multidrug resistance-associated protein (PfMRP2). Analysis proved the importance of a 4.1 kilo base pair sequence acting as a cis regulatory element controlling the timing of expression of the drug resistant gene. This gave rise to differential protein expression levels which associated with differential sensitivities of clones to antimalarial drugs - mefloquine and chloroquine. This is the first study in Plasmodium demonstrating the role of copy number polymorphisms in the intergenic promoters of drug resistant genes that result in drug-resistant phenotype and potentially can be used as a marker for mefloquine and chloroquine resistance in the field.